STARS WITH HIGH PROPER MOTIONS IN THE MODERN CATALOGS OF THE CDS DATABASE - Kryuchkovskiy, V. F.; Maigurova, N. V. (Одеські астрономічні публікації, 2016)
Stars with high proper motions, for the most part, are objects located in the solar neighborhood within 100 parsecs. These stars are important targets for a wide range of astrophysical problems, but the accuracy of the results depends on the completeness of the star samples. The uniform distribution over the celestial sphere is also important for kinematic studies. There are two catalogs of the fast stars in northern hemisphere, while only scattered lists of such stars are available for southern hemisphere. This paper presents the results of analysis of samples of stars with proper motions exceeding 150 mas/year from the modern catalogs of astronomical database CDS (PPMXL, SPM4, UCAC4, XPM, APOP, LSPM, Tycho2, URAT1 and WISE). Results of pairwise mutual crossidentification of the samples have shown that modern astrometric catalogs contain a significant number of false identifications of stars with large proper motions, and the total number of common stars in the resulting samples is extremely small and is not more than 20% on average.